2019
DOI: 10.3390/ma12111844
|View full text |Cite
|
Sign up to set email alerts
|

Half-Metallic Property Induced by Double Exchange Interaction in the Double Perovskite Bi2BB′O6 (B, B′ = 3d Transitional Metal) via First-Principles Calculations

Abstract: In this paper, we identify three possible candidate series of half-metals (HM) from Bi-based double perovskites Bi2BB′O6 (BB′ = transition metal ions) through calculations utilizing the density functional theory (DFT) and full-structural optimization, in which the generalized gradient approximation (GGA) and the strong correlation effect (GGA + U) are considered. After observing the candidate materials under four types of magnetic states, i.e., ferromagnetic (FM), ferrimagnetic (FiM), antiferromagnetic (AF), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Similarly, FiM-HM DP oxides of Bi 2 B′ZnO 6 (where B′ = Fe, Cr, Co) are also predicted from the theoretical calculations based on the GGA and GGA + U methods. 99…”
Section: Searching For Hm Materials In Dp Oxides From Theoretical And...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, FiM-HM DP oxides of Bi 2 B′ZnO 6 (where B′ = Fe, Cr, Co) are also predicted from the theoretical calculations based on the GGA and GGA + U methods. 99…”
Section: Searching For Hm Materials In Dp Oxides From Theoretical And...mentioning
confidence: 99%
“…Similarly, FiM-HM DP oxides of Bi 2 B 0 ZnO 6 (where B 0 = Fe, Cr, Co) are also predicted from the theoretical calculations based on the GGA and GGA + U methods. 99 Many advances have been achieved in theoretical investigations; in the parallel experimental direction some HM FiM DP oxides have been prepared in the forms of nanoparticles, thin films and bulks, and their local physical properties are also characterized at the nanoscale. For example, Zhao et al synthesized the FiM DP oxide Pb 2 FeOsO 6 (PFOO) by the solidstate reaction method under 8 GPa and 1673 K. 100 At 2 K, the measured M S value of the PFOO compound was 1.6m B per f.u.…”
Section: Hm Ferrimagnets In Dp Oxidesmentioning
confidence: 99%
“…Lin et al identified three prospective series of half-metals through first-principles calculations, considering generalized gradient approximation (GGA) and strong correlation effects (GGA + U) along with comprehensive structural characteristics. 28 Further exploration and development in the field of spintronics could potentially revolutionize information technology, giving rise to more efficient and versatile spintronic tools. The aim of this study is to gain insights into the features of Sr 2 AIrO 6 (A = Y, Lu, Sc) materials, encompassing their magnetic, elastic, thermodynamic and electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 To search for the novel materials with high T C , multiferroicity at RT as well as high spin polarization for spintronics devices, DP oxides like Sr-based Sr 2 B′B″O 6 (B′B″ = FeMo, FeRe, FeMn, FeW, CrMo, CrRe, CrW, and CrOs) [18][19][20][21][22][23][24][25] and Bi-based Bi 2 B′B″O 6 (B′B″ = NiMn, FeMn, CoMn, CoZn, FeCr, FeNi, FeZn, CrCo, CrNi, and CrZn) oxides have been widely investigated. [26][27][28][29][30] However, studies on the Ba-based DP oxides of Ba 2 B′B″O 6 (B′B″ = FeMn, FeMo, FeRe) are very limited. Recently, Ravi and Senthilkumar reported the synthesis of Ba 2 FeMnO 6 (BFMO) DP oxides by chemical combustion route.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of physical properties of DP oxides can be achieved by suitable combinations of the B′ and B″ ions 16,17 . To search for the novel materials with high T C , multiferroicity at RT as well as high spin polarization for spintronics devices, DP oxides like Sr‐based Sr 2 B′B″O 6 (B′B″ = FeMo, FeRe, FeMn, FeW, CrMo, CrRe, CrW, and CrOs) 18–25 and Bi‐based Bi 2 B′B″O 6 (B′B″ = NiMn, FeMn, CoMn, CoZn, FeCr, FeNi, FeZn, CrCo, CrNi, and CrZn) oxides have been widely investigated 26–30 . However, studies on the Ba‐based DP oxides of Ba 2 B′B″O 6 (B′B″ = FeMn, FeMo, FeRe) are very limited.…”
Section: Introductionmentioning
confidence: 99%